Investigation of Antibacterial Activity and Cytotoxicity of ZnO nanoparticles Synthesized by a Novel Biological Method - Shurooq S. Mahmood (Journal of Global Pharma Technology, 2016)
This research explains the biosynthesis, characterization, evaluation of the antibacterial activity and cytotoxicity of zinc oxide nanoparticles (ZnO NPs) prepared by a low-cost and simple procedure. Bio-inspired ZnO NPs were synthesized with the aid of a novel, non-toxic, ecofriendly biological material namely; Banana peels extract (BPE). Qualitative phytochemical screening of the aqueous fruit peels extract of Banana revealed the presence of many phytocomponents in it. The structural, morphological and optical properties of the synthesized nanoparticles have been characterized by using UV–Vis spectrophotometer, XRD, FE – SEM with EDX analysis, AFM, and FTIR. The synthesized ZnO NPs were characterized by a peak at 373 nm in the UV–Vis spectrum. The XRD of the sample revealed the hexagonal wurtzite structure with an average grain size 11.98 nm. Particle shapes and sizes were determined by FE-SEM. Surface morphology of the sample was studied by AFM. FT-IR confirmed the presence of functional groups of both leaf extract and ZnO NPs. The results showed the antibacterial activity of the ZnO NPs against Gram-positive bacteria (Staphylococcus aureus) and Gram-negative bacteria (Pseudomonas aeruginosa and Escherichia coli). The cytotoxicity of ZnO NPs was tested against vero101 normal cell line and skin A431 cancer cell line by Crystal violet (CV) assay. Banana peels mediated ZnO NPs showed no evidence of toxicity against normal cell line, the nanoparticles are biocompatible and are non-toxic and effective cytotoxic effect against cancer cell line. These results clearly support the benefits of using a biological method for synthesizing ZnO NPs with anticancer activities.Keywords: Zinc Oxide NPs; Biosynthesis; Banana peels extract (BPE); Phytochemical; Antibacterial; Cytotoxicity